Air‐Stable and High‐Performance Solution‐Processed Organic Light‐Emitting Devices Based on Hydrophobic Polymeric Ionic Liquid Carrier‐Injection Layers. Issue 18 (13th March 2018) - Sato, Shugo; Ohisa, Satoru; Hayashi, Yukihiro; Sato, Ryo; Yokoyama, Daisuke; Kato, Tetsuya; Suzuki, Michinori; Chiba, Takayuki; Pu, Yong‐Jin; Kido, Junji
Abstract: A lot of research, mostly using electron‐injection layers (EILs) composed of alkali‐metal compounds has been reported with a view to increase the efficiency of solution‐processed organic light‐emitting devices (OLEDs). However, these materials have intractable properties, such as a strong affinity for moisture, which cause the degradation of OLEDs. Consequently, optimal EIL materials should exhibit high electron‐injection efficiency as well as be stable in air. In this study, polymer light‐emitting devices (PLEDs) based on the commonly used yellow‐fluorescence‐emitting polymer F8BT, which utilize poly(diallyldimethylammonium)‐based polymeric ionic liquids, are experimentally and analytically investigated. As a result, the optimized PLED employing an EIL comprising poly(diallyldimethylammonium) bis(trifluoromethanesulfonyl)imide (poly(DDA)TFSI), which is expected to display good moisture resistance because of water repellency of fluorocarbon groups, exhibits excellent storage stability in air and electroluminescence performance with a low turn‐on voltage of 2.01 V, maximum external quantum efficiency of 9.00%, current efficiency of 30.1 cd A −1, and power efficiency of 32.4 lm W −1 . The devices with poly(DDA)TFSI show one of the highest efficiencies as compared to the reported standard PLEDs. Moreover, poly(DDA)TFSI is applied as a hole‐injection layer (HIL). The optimized PLED using poly(DDA)TFSI as the HIL exhibits performances comparable to those of a device that uses a conventional poly(3, 4‐ethylenedioxy‐thiophene):poly(4‐styrenesulfonate) HIL. Abstract : Hydrophobic polymeric ionic liquids, poly(diallyldimethylammonium) bis(trifluoromethanesulfonyl)imide (poly(DDA)TFSI) exhibit good work‐function tunability and hydrophobic property. Polymer light‐emitting devices with poly(DDA)TFSI as the electron‐injection layer achieve excellent air‐storage stability and electroluminescence with a low turn‐on voltage of 2.01 V and maximum external quantum efficiency, current efficiency, and power efficiency values of 9.00%, 30.1 cd A −1, and 32.4 lm W −1 .